2018
DOI: 10.1016/j.bbi.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beta-adrenergic blockade on inflammatory and cardiovascular responses to acute mental stress

Abstract: HighlightsThe mechanisms underlying acute stress-induced IL-6 responses are poorly understood.We assessed the effects of beta-blockade with propranolol in a double-blind study.Beta-blockade reduced IL-6 responses to stress in men but not women.Blood pressure and heart rate responses was not affected by propranolol.The study provides partial support for SNS involvement in stress-induced inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…[6,32,33] The depression rate found in this study (30%) was a little bit higher than in the general population (20%) [34] and is probably explained by the cognitive impairment in the glioblastoma population. The interaction of beta-blockers with the adrenergic pathway involved in stress and depression has been the subject of many publications concerning their impact on these pathologies [35][36][37][38] and the proportion of patients treated with beta-blockers in our study seems similar to the proportion observed in the general population (20%). [39] Location of the tumour did not impact stress, especially frontal location that can induce hypersensitivity which can lead to organic depression and anosodiaphoria which can lead to emotional indifference.…”
Section: Discussionsupporting
confidence: 79%
“…[6,32,33] The depression rate found in this study (30%) was a little bit higher than in the general population (20%) [34] and is probably explained by the cognitive impairment in the glioblastoma population. The interaction of beta-blockers with the adrenergic pathway involved in stress and depression has been the subject of many publications concerning their impact on these pathologies [35][36][37][38] and the proportion of patients treated with beta-blockers in our study seems similar to the proportion observed in the general population (20%). [39] Location of the tumour did not impact stress, especially frontal location that can induce hypersensitivity which can lead to organic depression and anosodiaphoria which can lead to emotional indifference.…”
Section: Discussionsupporting
confidence: 79%
“…There are also differences in autonomic reactivity to stress between males and females, with females demonstrating a lower adrenergic response to mental stress than males. 4,5 Repolarization Bazette first noted longer QT interval in females in 1920, 6 and this has been confirmed subsequently. 7…”
Section: Conductionmentioning
confidence: 79%
“…Beta-blockers reduce the mortality in cardiac diseases by attenuating the deleterious effects of sympathetic hyperactivation and increasing the vagal tone [84]. In sepsis, betablockers improve HR control, reduce systemic inflammation, and decrease mortality, acknowledging that their routine use is not yet warranted [85,86].…”
Section: Prognostic Value Of Brainstem Dysfunction and Therapeutic Pementioning
confidence: 99%